A moderate level of hypovirulence conferred by a hypovirus in the avocado white root rot fungus, Rosellinia necatrix - Arjona-López, Juan M.; Telengech, Paul; Suzuki, Nobuhiro; López-Herrera, Carlos J. (Fungal biology, 2021)
Two isolates of Rosellinia necatrix (Rn118-8 and Rn480) have previously obtained from diseased avocado trees in commercial orchards of the coastal area in southern Spain. Rn118-8 and Rn480 have weak virulence on avocado plants, and are infected by R. necatrix hypovirus 2 (RnHV2). In this work, the possible biological effects of the hypovirus on R. necatrix were tested. First, RnHV2 was transmitted from each of Rn118-8 and Rn480 to a highly virulent, RnHV2-free isolate of R. necatrix (Rn400) through hyphal anastomosis, using zinc compounds which attenuate the mycelial incompatibility reactions and allow for horizontal virus transfer between vegetatively incompatible fungal strains. Next, we carried out an analysis of growth rate in vitro and a virulence test of these newly infected strains in avocado plants. We obtained five strains of Rn400 infected by RnHV2 after horizontal transmission, and showed some of them to have lower colony growth in vitro and lower virulence on avocado plants compared with virus-free Rn400. These results suggest that R. necatrix isolates infected by RnHV2 could be used as novel virocontrol agents to combat avocado white root rot. •Two Rosellinia necatrix isolates infected by RnHV2 showed low virulence on avocado plants.•RnHV2 was transmitted to R. necatrix virus-free isolate (Rn400) using zinc compounds.•RnHV2 reduced the colony growth in vitro and the virulence of Rn400 on avocado plants.